Influence of the liposomal preparation Butaintervite on protein synthesis function in the livers of rats under the influence of carbon tetrachloride poisoning - M. I. Hariv; B. V. Gutyj (Regulatory Mechanisms in Biosystems, 2016)
This article presents the results of research into the influence of the complex liposomal preparation Butaintervit on protein synthesis function in the livers of rats under the influence of carbon tetrachloride poisoning. Intramuscular injection of carbon tetrachloride into rats at a dose of 0.25 ml per100 gof body weight causes antigenic load on the body and leads to disruption of protein synthesis function in the liver. This is shown by reduction in blood levels of total protein and its fractions. Thus, the level of albumin in the serum of rats under the conditions of oxidative stress was 70% lower than in clinically healthy animals. However, the level of total protein in the serum was only 10% lower. This is because, along with the decrease of albumin content in the serum, the levels of globulin protein fraction increased by 8.8%. This has led to albumin/globulin disparities in the serum of sick animals. As a result, the value of A/G coefficient was 0.28 ± 0.03, compared to 0.52 ±0.02 inclinically healthy rats. For the normalization of functional state of the liver under oxidative stress it is advisable to apply the liposomal preparation Butaintervite, which in its structure contains butafosfan, interferon, thistle and vitamins A, D and E. Under conditions of oxidative stress and under the action of the liposomal preparation in the rats from the second experimental group we have found significant increase in the levels of total protein and albumins and a decrease in serum globulin in the animals on the fifth and tenth days of the experiment. On the fourteenth day of the experiment under the conditions of oxidative stress and under the action of the liposomal preparation in the rats from the second experimental group the normalization of protein synthesis function in the liver was observed. The level of indicators of total protein, albumin, globulin and the coefficient of albumin/globulin compared with the control group of animals were within normal values.